La imagen corporativa y el posicionamiento de la empresa ICOPLAST de la ciudad de Riobamba, período junio 2016 - junio 2017 - Pilataxi León, Carmen Victoria (2018)
The name of this research is corporate image in ICOPLAST Company positioning, in Riobamba city, from June 2016 to June 2017. The objective of this research is to determine corporate image in ICOPLAST Company positioning in Riobamba city. This research has been developed under theoretical framework based on its research variables. The firs one is Corporate image which accounts for marketing theories. The second variable is Company positioning which discusses different management theories. In the field research, an enterprise analysis was carried out by applying FODA technique. The mentioned study allowed to arise three strategic objectives which underpin the enterprise success. On the other hand, a survey was applied in order to gather information from external users. The survey results account for corporate image incidence about its production commercialization. Therefore, a lack of strategic planning for commercialization does not allow ICOPLAST enterprise to be well known around local and national market.